Produção científica e questões teórico-metdológicas dos líderes dos grupos de pesquisa com ênfase no campo do currículo inscritos no Diretório de Grupos do CNPq/Brasil - MATOS, Cleide Carvalho de (Universidade Federal do Pará, 2017)
This paper aims to research the scientific production and theoretical-methodological perspectives of the leaders of research groups in the field of curriculum. The purpose was to analyze the prominent theoretical-methodological perspectives in the area of the curriculum from the scientific productions of the leaders of research groups that chose the curriculum as object of study. What is the configuration of the research groups, with emphasis in the area of the curriculum, registered in the CNPq directory? Do the scientific productions of the leaders of the research groups that focus on the curriculum as objects of study and research prioritize the themes? What are the theoretical-methodological perspectives that tint the curriculum as an object of the scientific production of the leaders of the research groups? Documentary sources focused on the indicators on research groups available in the National Council of Scientific and Technological Development (CNPq) Group Directory Database and the Lattes curriculum of the leaders of these scientific spaces. I agree with authors such as: Bourdieu (2005; 2004) Corrêa (2013; 2012), Moreira (2001, 1990), Silva (2004, 1990), Ferreira Junior (2010) and Hayashi (2007). The historical time span of the research comprised the interstice between 1992 and 2014. The theoretical-methodological perspectives adopted by the leaders of the research groups show that the theoretical "frontiers" are in movement, becoming space of exchange, symbiosis, construction Of new conceptual relationships. There is concomitant use of critical and post-critical, structural and post-structural, post-structural and post-modern, post-structural and post-colonial discourses. The scientific field of the curriculum is evidenced as a space of dispute mobilizing forces that propagate generating institutional asymmetries and zones of privilege. The holders of scientific authority hold prominent positions in the institutional spaces in which they maintain employment relationships and in the field of curriculum.